AB0558 Are regulatory t cell levels different in active and inactive sle patients?. (12th June 2018) - Üsküdar Teke, H.; Üsküdar Cansu, D.; Bal, C.; Korkmaz, C.
Abstract : Background: The subgroups of T helper cells and regulatory T cells (T-reg) are involved in the pathogenesis of systemic lupus erythematosus (SLE). T-reg cells suppress immune response to autoantigens and prevent autoimmune diseases (AID). Although there are studies suggesting that Treg cells are reduced during the active period of SLE, there are also studies claiming reversal. Objectives: To determine whether there is a difference between T-reg and Th-17 cell levels in active and inactive SLE patients and to demonstrate the effects of these cells on disease course. Methods: 21 SLE patients without active infection were included. Erythrocyte sedimentation rate, CRP, C3, C4, anti-ds-DNA levels, SLEDAI values were recorded in terms of organ and system involvement, hemogram results, disease activation. SLEDAI ≥6 were considered active disease. Concurrent peripheral blood Th17 and T-reg levels were studied. 15 healthy control subjects were included in the study. Results: 19 of the patients were women, the mean age was 37.3±12.9 years and mean duration of the disease was 7.9±1.29 years. Hematologic involvement was present in 15 (71.4%) of the patients, renal involvement in 17 (81%) and joint involvement in 7 (42.9%). Both Treg cells and CD4 +IL17+cell levels were significantly higher in SLE group than HC group in terms of CD4 +CD25+, CD4 +FOXP3+T reg, CD4 +CD25+FOXP3+T reg (p=0.011, p=0.001, p=0.001 and p=0.040, respectively). There was no significant difference between active (n=12) and inactive (n=9) SLE patients in terms of Th17 and T-reg levels. However, in the inactive period, the levels of CD4 +FOXP3+T reg and CD4 +CD25+FOXP3+Treg cells tended to increase compared to the active period. Conclusions: This study showed the tendency of increasing in Treg cells in the inactive period. This may be related to the modification of immunosuppressive drugs. It may be more appropriate to perform similar studies before and after treatment. Disclosure of Interest: None declared